(untitled) (International Seven Journal of Health Research, 2024)
Melasma is a hyperpigmentation disorder that mainly affects women. Factors such as chronic exposure to ultraviolet radiation, visible light, hormonal stimulation and genetic factors have been identified in its pathogenesis. It is characterized by reticulated, irregular, brown spots on areas of the skin exposed to the sun. The methodology used was a literature review with an exploratory qualitative approach, using academic platforms and bibliographies: SCIELO, PUB MED and GOOGLE ACADEMICO. The inclusion criteria were articles from recent years in Portuguese and English. The correct use of sunscreens can prevent the appearance of melasma, which in turn prevents skin cancer. Sunscreen helps block solar radiation, preventing dischromic spots that ultraviolet rays cause on the skin, and there are different factors for each skin type; always reapply every two hours and it is important to know that the use of sunscreen begins in childhood, as damage accumulates on the skin, causing complications in adulthood, such as skin cancer. It can be concluded that the use of accessories such as hats, umbrellas and sunscreens help prevent dyschromia.